(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
The Mobile applications designed for An droid frequently have access to private information and re sources stored on the user’s device. The improper use of this data by malicious programs has the potential to result in breaches of privacy as well as the disclosure of sensitive data. An example of this would be a malicious application capturing a confidential business chat in the background without the user’s knowledge. The issue is caused by the fact that Android users do not have control over the capabilities of programs once those applications have been granted the desired access during installation. This is what causes the problem. It is necessary for us to have a context-based ac cess control mechanism so that privileges can be dynamical ly provided or revoked to applications based on the specific context of the user. This is because there are numerous situa tions in which the possibility that an application will be al lowed a privilege is contingent on the specific context of the user. In this article, we suggest an access control system along these lines. Our implementation of context distin guishes between subareas that are geographically adjacent to one another within the same location. We have made certain changes to the Android operating system in order to enable context-based access control limitations, which can then be set and implemented. We have carried out a number of tests in order to evaluate both the efficacy of our access control mechanism and the precision of context recognition.